FAIRCLOUGH, NORMAN (2006). Language and globalization - Resende, Viviane de Melo (Revista Latinoamericana de Estudios del Discurso, 2020)
FAIRCLOUGH, NORMAN (2006). Language and globalization. London, Routledge. 186 pp. ISBN 10: 0-415-31765-7